PERANCANGAN SISTEM INFORMASI MONITORING PROGRES PENGADAAN BARANG PADA BAGIAN PENGADAAN DAN LOGISTIK INSTITUT INFORMATIKA DAN BISNIS DARMAJAYA - Sutedi Sutedi (Jurnal Informatika, 2011)
Institute of Information Technology and Business Darmajaya is a leading private college fast growing and should be balanced with meeting facilities and infrastructure as well. Managing the procurement function is handled by the Procurement and Logistics Sections that have applied computer technology in assisting the administration of the procurement process. To improve performance and simplify the process of monitoring the progress of procurement of goods, it is necessary to build the information system monitoring the progress of the procurement is expected to facilitate the stretcher in overseeing and ensuring the procurement process is run in accordance with the agreed terms. Information systems development is done using structured analysis and design methodology. Keywords: Monitoring, Procurement, Information Systems